Formula and preparation method of laundry fiber wrappage with high surfactant content
Through the high surfactant content laundry fiber wrap formula, the synergistic effect of multiple surfactants and biological enzymes is used to solve the problems of poor cleaning effect and major damage to clothes in existing washing products, achieving stronger decontamination Ability and clothing protection effect.
Patent Information
- Application Number
- CN202411394264.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing washing products have poor cleaning results when facing stubborn stains and cause great damage to clothes, resulting in poor washing effect and strong destructiveness.
Using a high surfactant content laundry fiber encapsulation formula, the molding agent is prepared through the synergistic action of mixed anionic surfactants, nonionic surfactants, green chelating agents, anti-redeposition agents, detergent additives and biological enzymes. Press it onto the nonwoven fabric to form an efficient laundry fiber wrap.
It significantly improves the decontamination effect and overall washing performance, extends the service life of clothes, and reduces damage to clothes.
Smart Images

Figure BDA0005073294840000021 
Figure BDA0005073294840000141 
Figure BDA0005073294840000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of detergents, and in particular relates to a formula of a laundry fiber wrapping material with a high surfactant content and a preparation method thereof. Background Art
[0002] In daily life, we often use various types of washing products to clean clothes. Among them, conventional laundry detergents are often powerless and the cleaning effect is unsatisfactory due to their relatively low content of surfactants and usually contain no or only a small amount of detergent aids when facing some stubborn stains. Although concentrated laundry detergents and laundry beads have a higher surfactant content and can provide stronger cleaning power, due to the limitations of their dosage forms, they cannot add a large amount of chelating agents and other detergent aids. As a result, when faced with some specific heavy oil dirt, colored dirt and granular dirt, their performance is often unsatisfactory and the cleaning effect is relatively weak. As for laundry powder, although it performs relatively well in terms of cleaning power, its content of surfactants is low and it contains a large amount of inorganic salt additives, which causes greater damage to clothes during the washing process and easily leads to wear and deformation of clothing fibers. Summary of the invention
[0003] The object of the present invention is to provide a formula of a laundry fiber wrapping material with a high surfactant content and a preparation method thereof, so as to solve the problem that the existing laundry products have poor laundry washing effect and strong destructiveness to the laundry.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A formula of a laundry fiber wrap with a high surfactant content, comprising the following raw materials in parts by weight:
[0006]
[0007]
[0008] As a preferred technical solution of the present invention, the preparation method of the molding agent comprises the following steps:
[0009] S1. Mix aluminum chloride hexahydrate, sodium hydroxide and deionized water, heat in a 60°C water bath with stirring for 2-4 hours, and then heat in a 60°C water bath and stand for 20-30 hours to obtain material A;
[0010] S2, take the material A and nano bentonite (purchased from Wuhan Kanosi Technology Co., Ltd.) and mix them, heat in a 60°C water bath with stirring for 4-6h, then heat in a 60°C water bath and stand for 10-14h, centrifuge, wash the solid phase, dry, grind, and pass through a 150-mesh sieve to obtain material B;
[0011] S3, take ammonium fluoride, tetrabutyl titanate, and anhydrous ethanol, mix, stir for 10-15 minutes, add glacial acetic acid and acetylacetone in sequence, continue stirring for 4-5 hours, let stand for 20-30 hours, filter, wash the solid phase, dry, place in a muffle furnace at 300-400 ° C for 2-3 hours, cool, grind, and pass through a 150 mesh sieve to obtain material C;
[0012] S4, taking the material B and deionized water, mixing, ultrasonically dispersing for 15-25 minutes, adding sodium fluoride, heating in a water bath at 80°C with stirring for 2-3 hours, stopping heating, adding sodium bicarbonate, ultrasonically dispersing for 25-35 minutes, centrifuging, taking the solid phase, drying, grinding, and passing through a 150-mesh sieve to obtain material D;
[0013] S5. Mix the material C, material D and deionized water, disperse them by ultrasonication for 1-2 hours, let them stand for 10-12 hours, filter them, wash the solid phase and dry them to obtain the molding agent.
[0014] As a preferred technical solution of the present invention, in step S1, the mass ratio of aluminum chloride hexahydrate, sodium hydroxide and deionized water is 1.2-1.4:0.9-1.1:20.
[0015] As a preferred technical solution of the present invention, in step S2, the dosage ratio of the material A and the nano-bentonite is 10-12 mL: 6-8 g.
[0016] As a preferred technical solution of the present invention, in step S3, the dosage ratio of ammonium fluoride, tetrabutyl titanate, anhydrous ethanol, glacial acetic acid and acetylacetone is 1-1.6 g: 20-25 mL: 60-80 mL: 3-5 mL: 5-6 mL.
[0017] As a preferred technical solution of the present invention, in step S4, the mass ratio of material B, deionized water, sodium fluoride and sodium bicarbonate is 20-25:300:1-3:2-4.
[0018] As a preferred technical solution of the present invention, in step S5, the mass ratio of material C, material D and deionized water is 0.6-0.8:3-4:50.
[0019] As a preferred technical solution of the present invention, the polyvinyl alcohol nonwoven fabric is a fiber cloth made of polyvinyl alcohol with a polymerization degree of 500-800 and an alcoholysis degree of 80-90.
[0020] As a preferred technical solution of the present invention, the mixed anionic surfactant includes sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate; the mass ratio of sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate is 5-7:4-6:2-3:1-2:2-3;
[0021] The nonionic surfactant comprises fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside; the mass ratio of the fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside is 6-8:3-4:1-2;
[0022] The green chelating agent comprises trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate; the mass ratio of trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate is 7-9:7-9:3-4:1-2;
[0023] The anti-redeposition agent comprises sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer; the mass ratio of the sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer is 2-3:2-3:1-2;
[0024] The washing aid comprises sodium carbonate, sodium bicarbonate and sodium silicate; the mass ratio of the sodium carbonate, sodium bicarbonate and sodium silicate is 2-3:2-3:2-3;
[0025] The biological enzymes include protease, lipase, amylase, cellulase and pectinase; the mass ratio of the protease, lipase, amylase, cellulase and pectinase is 6-8:6-8:5-7:2-3:2-3.
[0026] A method for preparing a laundry fiber package with a high surfactant content, the method comprising the following steps:
[0027] A mixed anionic surfactant, a nonionic surfactant, a green chelating agent, an anti-redeposition agent, a detergent aid and a forming agent are mixed according to the formula amount, stirred for 4-6 hours, allowed to stand for 10-12 hours, polyethylene glycol 4000, cellulose and fatty acid are added, heated and stirred at 50° C. for 20-30 minutes to obtain a viscous material body, the viscous material body is pressed onto a polyvinyl alcohol nonwoven fabric with a gap width of 0.5 mm*0.5 mm-1 mm*1 mm, the viscous material body is cooled to below 40° C., the biological enzyme is evenly mixed and sprayed on the surface of the viscous material body, another polyvinyl alcohol nonwoven fabric with a gap width of 0.1 mm*0.1 mm-0.3 mm*0.3 mm is pressed onto the surface of the viscous material body, cooled, sliced and packaged to obtain the laundry fiber package with a high surfactant content.
[0028] Beneficial effects of the present invention:
[0029] The formula of a laundry fiber wrapping with a high surfactant content disclosed in the present invention and the preparation method thereof increase the wrapping amount of the surfactant components and improve the decontamination effect by preparing a molding agent with a strong adsorption effect on the surfactant components; the decontamination effect can be significantly improved by the synergistic effect of adding multiple anionic surfactants; the overall washing performance is enhanced by the synergistic effect of adding multiple nonionic surfactants; and the decontamination effect is improved by adding multiple biological enzymes, and the service life of the clothes can also be extended. DETAILED DESCRIPTION
[0030] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0031] Example 1
[0032] A method for preparing a laundry fiber package with a high surfactant content comprises the following steps:
[0033] According to the formula, 30 parts by mass of a mixed anionic surfactant, 20 parts by mass of a nonionic surfactant, 10 parts by mass of a green chelating agent, 1 part by mass of an anti-redeposition agent, 10 parts by mass of a detergent aid and 10 parts by mass of a forming agent are mixed, stirred for 4 hours, allowed to stand for 10 hours, 50 parts by mass of polyethylene glycol 4000, 4 parts by mass of cellulose and 1 part by mass of a fatty acid are added, and the mixture is heated and stirred at 50° C. for 20 minutes to obtain a viscous material body, and the viscous material body is pressed onto a 2.5-part polyvinyl alcohol nonwoven fabric with a gap width of 0.5 mm*0.5 mm, and the viscous material body is cooled to below 40° C., the biological enzyme is evenly mixed and sprayed on the surface of the viscous material body, and another 2.5-part polyvinyl alcohol nonwoven fabric with a gap width of 0.1 mm*0.1 mm is pressed onto the surface of the viscous material body, cooled, sliced and packaged to obtain the laundry fiber package with a high surfactant content.
[0034] The preparation method of the molding agent comprises the following steps:
[0035] S1. Mix aluminum chloride hexahydrate, sodium hydroxide and deionized water, heat in a water bath at 60°C with stirring for 2 hours, and then heat in a water bath at 60°C and stand for 20 hours to obtain material A; the mass ratio of aluminum chloride hexahydrate, sodium hydroxide and deionized water is 1.2:0.9:20;
[0036] S2, taking the material A and the nano-bentonite, mixing them, heating in a water bath at 60°C with stirring for 4 hours, then heating in a water bath at 60°C and standing for 10 hours, centrifuging, washing the solid phase, drying, grinding, and passing through a 150-mesh sieve to obtain material B; the dosage ratio of the material A to the nano-bentonite is 10 mL: 6 g;
[0037] S3, take ammonium fluoride, tetrabutyl titanate, and anhydrous ethanol, mix, stir for 10 minutes, add glacial acetic acid and acetylacetone in turn, continue stirring for 4 hours, let stand for 20 hours, filter, wash the solid phase, dry, place in a muffle furnace at 300 ° C for 2 hours, cool, grind, and pass through a 150 mesh sieve to obtain material C; the amount ratio of ammonium fluoride, tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, and acetylacetone is 1g:20mL:60mL:3mL:5mL;
[0038] S4, take the material B, mix it with deionized water, ultrasonically disperse it for 15 minutes, add sodium fluoride, heat it in a water bath at 80°C and stir it for 2 hours, stop heating, add sodium bicarbonate, ultrasonically disperse it for 25 minutes, centrifuge it, take the solid phase and dry it, grind it, and pass it through a 150-mesh sieve to obtain material D; the mass ratio of the material B, deionized water, sodium fluoride and sodium bicarbonate is 20:300:1:2;
[0039] S5. Mix the material C, material D and deionized water, perform ultrasonic dispersion for 1 hour, let stand for 10 hours, filter, wash the solid phase, and dry to obtain the molding agent; the mass ratio of the material C, material D and deionized water is 0.6:3:50.
[0040] The polyvinyl alcohol nonwoven fabric is a fiber fabric made of polyvinyl alcohol with a polymerization degree of 500 and an alcoholysis degree of 80.
[0041] The mixed anionic surfactant comprises sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate; the mass ratio of the sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate is 5:4:2:1:2;
[0042] The nonionic surfactant comprises fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside; the mass ratio of the fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside is 6:3:1;
[0043] The green chelating agent comprises trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate; the mass ratio of trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate is 7:7:3:1;
[0044] The anti-redeposition agent comprises sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer; the mass ratio of the sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer is 2:2:1;
[0045] The washing aid comprises sodium carbonate, sodium bicarbonate and sodium silicate; the mass ratio of the sodium carbonate, sodium bicarbonate and sodium silicate is 2:2:2;
[0046] The biological enzymes include protease, lipase, amylase, cellulase and pectinase; the mass ratio of the protease, lipase, amylase, cellulase and pectinase is 6:6:5:2:2.
[0047] Example 2
[0048] A method for preparing a laundry fiber package with a high surfactant content comprises the following steps:
[0049] According to the formula, 40 parts by mass of a mixed anionic surfactant, 25 parts by mass of a nonionic surfactant, 15 parts by mass of a green chelating agent, 3 parts by mass of an anti-redeposition agent, 15 parts by mass of a detergent aid and 15 parts by mass of a forming agent are mixed, stirred for 5 hours, allowed to stand for 11 hours, 50 parts by mass of polyethylene glycol 4000, 5 parts by mass of cellulose and 1.5 parts by mass of a fatty acid are added, and the mixture is heated and stirred at 50° C. for 25 minutes to obtain a viscous material body, and the viscous material body is pressed onto a 4-part polyvinyl alcohol nonwoven fabric with a gap width of 0.8 mm*0.8 mm8, and the viscous material body is cooled to below 40° C., the biological enzyme is evenly mixed and sprayed on the surface of the viscous material body, and another 4-part polyvinyl alcohol nonwoven fabric with a gap width of 0.2 mm*0.2 mm is pressed onto the surface of the viscous material body, cooled, sliced and packaged to obtain the laundry fiber package with a high surfactant content.
[0050] The preparation method of the molding agent comprises the following steps:
[0051] S1. Mix aluminum chloride hexahydrate, sodium hydroxide and deionized water, heat in a water bath at 60°C with stirring for 3 hours, and then heat in a water bath at 60°C and stand for 25 hours to obtain material A; the mass ratio of aluminum chloride hexahydrate, sodium hydroxide and deionized water is 1.3:1:20;
[0052] S2, taking the material A and the nano-bentonite, mixing them, heating in a water bath at 60°C with stirring for 5 hours, then heating in a water bath at 60°C and standing for 12 hours, centrifuging, washing the solid phase, drying, grinding, and passing through a 150-mesh sieve to obtain material B; the dosage ratio of the material A to the nano-bentonite is 11 mL: 7 g;
[0053] S3, take ammonium fluoride, tetrabutyl titanate, and anhydrous ethanol, mix, stir for 13 minutes, add glacial acetic acid and acetylacetone in turn, continue stirring for 4.5 hours, let stand for 25 hours, filter, wash the solid phase, dry, place in a muffle furnace at 350 ° C for 2.5 hours, cool, grind, and pass through a 150 mesh sieve to obtain material C; the amount ratio of ammonium fluoride, tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, and acetylacetone is 1.3g:22mL:70mL:4mL:5.5mL;
[0054] S4, take the material B, deionized water, mix, ultrasonically disperse for 20 minutes, add sodium fluoride, heat in a water bath at 80°C with stirring for 2.5 hours, stop heating, add sodium bicarbonate, ultrasonically disperse for 30 minutes, centrifuge, take the solid phase, dry, grind, and pass through a 150-mesh sieve to obtain material D; the mass ratio of the material B, deionized water, sodium fluoride, and sodium bicarbonate is 22:300:2:3;
[0055] S5. Mix the material C, material D and deionized water, perform ultrasonic dispersion for 1.5 hours, let stand for 11 hours, filter, wash the solid phase, and dry to obtain the molding agent; the mass ratio of the material C, material D and deionized water is 0.7:3.5:50.
[0056] The polyvinyl alcohol nonwoven fabric is a fiber fabric made of polyvinyl alcohol with a polymerization degree of 700 and an alcoholysis degree of 85.
[0057] The mixed anionic surfactant comprises sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate; the mass ratio of sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate is 6:5:2.5:1.5:2.5;
[0058] The nonionic surfactant comprises fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside; the mass ratio of the fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside is 7:3.5:1.5;
[0059] The green chelating agent comprises trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate; the mass ratio of trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate is 8:8:3.5:1.5;
[0060] The anti-redeposition agent comprises sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer; the mass ratio of the sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer is 2.5:2.5:1.5;
[0061] The washing aid comprises sodium carbonate, sodium bicarbonate and sodium silicate; the mass ratio of the sodium carbonate, sodium bicarbonate and sodium silicate is 2.5:2.5:2.5;
[0062] The biological enzymes include protease, lipase, amylase, cellulase and pectinase; the mass ratio of the protease, lipase, amylase, cellulase and pectinase is 7:7:6:2.5:2.5.
[0063] Example 3
[0064] A method for preparing a laundry fiber package with a high surfactant content comprises the following steps:
[0065] According to the formula, 50 parts by mass of a mixed anionic surfactant, 30 parts by mass of a nonionic surfactant, 20 parts by mass of a green chelating agent, 5 parts by mass of an anti-redeposition agent, 20 parts by mass of a detergent aid and 20 parts by mass of a forming agent are mixed, stirred for 6 hours, allowed to stand for 12 hours, 50 parts by mass of polyethylene glycol 4000, 6 parts by mass of cellulose and 2 parts by mass of a fatty acid are added, and the mixture is heated and stirred at 50° C. for 30 minutes to obtain a viscous material body, and the viscous material body is pressed onto a 5-part polyvinyl alcohol nonwoven fabric with a gap width of 1 mm*1 mm, and the viscous material body is cooled to below 40° C., the biological enzyme is evenly mixed and sprayed on the surface of the viscous material body, and another 5-part polyvinyl alcohol nonwoven fabric with a gap width of 0.3 mm*0.3 mm is pressed onto the surface of the viscous material body, cooled, sliced and packaged to obtain the laundry fiber package with a high surfactant content.
[0066] The preparation method of the molding agent comprises the following steps:
[0067] S1. Mix aluminum chloride hexahydrate, sodium hydroxide and deionized water, heat in a water bath at 60°C with stirring for 4 hours, and then heat in a water bath at 60°C and stand for 30 hours to obtain material A; the mass ratio of aluminum chloride hexahydrate, sodium hydroxide and deionized water is 1.4:1.1:20;
[0068] S2, taking the material A and the nano-bentonite, mixing them, heating in a water bath at 60°C with stirring for 6 hours, then heating in a water bath at 60°C and standing for 14 hours, centrifuging, washing the solid phase, drying, grinding, and passing through a 150-mesh sieve to obtain material B; the dosage ratio of the material A to the nano-bentonite is 12mL:8g;
[0069] S3, take ammonium fluoride, tetrabutyl titanate, and anhydrous ethanol, mix, stir for 15 minutes, add glacial acetic acid and acetylacetone in turn, continue stirring for 5 hours, let stand for 30 hours, filter, wash the solid phase, dry, place in a muffle furnace at 400 ° C for 3 hours, cool, grind, and pass through a 150 mesh sieve to obtain material C; the amount ratio of ammonium fluoride, tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, and acetylacetone is 1.6g:25mL:80mL:5mL:6mL;
[0070] S4, take the material B, mix it with deionized water, ultrasonically disperse it for 25 minutes, add sodium fluoride, heat it in a water bath at 80°C and stir it for 3 hours, stop heating, add sodium bicarbonate, ultrasonically disperse it for 35 minutes, centrifuge it, take the solid phase and dry it, grind it, and pass it through a 150-mesh sieve to obtain material D; the mass ratio of the material B, deionized water, sodium fluoride and sodium bicarbonate is 25:300:3:4;
[0071] S5. Mix the material C, material D and deionized water, perform ultrasonic dispersion for 2 hours, let stand for 12 hours, filter, wash the solid phase, and dry to obtain the molding agent; the mass ratio of the material C, material D and deionized water is 0.8:4:50.
[0072] The polyvinyl alcohol nonwoven fabric is a fiber fabric made of polyvinyl alcohol with a polymerization degree of 800 and an alcoholysis degree of 90.
[0073] The mixed anionic surfactant comprises sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate; the mass ratio of the sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium cocoate, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate is 7:6:3:2:3;
[0074] The nonionic surfactant comprises fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside; the mass ratio of the fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glucoside is 8:4:2;
[0075] The green chelating agent comprises trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate; the mass ratio of trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate is 9:9:4:2;
[0076] The anti-redeposition agent comprises sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer; the mass ratio of the sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer is 3:3:2;
[0077] The washing aid comprises sodium carbonate, sodium bicarbonate and sodium silicate; the mass ratio of the sodium carbonate, sodium bicarbonate and sodium silicate is 3:3:3;
[0078] The biological enzymes include protease, lipase, amylase, cellulase and pectinase; the mass ratio of the protease, lipase, amylase, cellulase and pectinase is 8:8:7:3:3.
[0079] Comparative Example 1
[0080] The difference from Example 1 is that the preparation method of the molding agent comprises the following steps:
[0081] S1. Mix ammonium fluoride, tetrabutyl titanate and anhydrous ethanol, stir for 10 min, add glacial acetic acid and acetylacetone in sequence, continue stirring for 4 h, let stand for 20 h, filter, wash the solid phase, dry, place in a muffle furnace and roast at 300 ° C for 2 h, cool, grind, and pass through a 150 mesh sieve to obtain material C; the dosage ratio of ammonium fluoride, tetrabutyl titanate, anhydrous ethanol, glacial acetic acid and acetylacetone is 1 g: 20 mL: 60 mL: 3 mL: 5 mL;
[0082] S2, mix nano-bentonite and deionized water, ultrasonically disperse for 15 minutes, add sodium fluoride, heat and stir in a water bath at 80°C for 2 hours, stop heating, add sodium bicarbonate, ultrasonically disperse for 25 minutes, centrifuge, dry the solid phase, grind, and pass through a 150-mesh sieve to obtain material D; the mass ratio of the nano-bentonite, deionized water, sodium fluoride, and sodium bicarbonate is 20:300:1:2;
[0083] S3. Mix the material C, material D and deionized water, perform ultrasonic dispersion for 1 hour, let stand for 10 hours, filter, wash the solid phase and dry to obtain the molding agent; the mass ratio of the material C, material D and deionized water is 0.6:3:50.
[0084] Comparative Example 2
[0085] The difference from Example 1 is that the preparation method of the molding agent comprises the following steps:
[0086] S1. Mix aluminum chloride hexahydrate, sodium hydroxide and deionized water, heat in a water bath at 60°C with stirring for 2 hours, and then heat in a water bath at 60°C and stand for 20 hours to obtain material A; the mass ratio of aluminum chloride hexahydrate, sodium hydroxide and deionized water is 1.2:0.9:20;
[0087] S2, taking the material A and the nano-bentonite, mixing them, heating in a water bath at 60°C with stirring for 4 hours, then heating in a water bath at 60°C and standing for 10 hours, centrifuging, washing the solid phase, drying, grinding, and passing through a 150-mesh sieve to obtain material B; the dosage ratio of the material A to the nano-bentonite is 10 mL: 6 g;
[0088] S3. Mix the material B and deionized water, disperse ultrasonically for 15 minutes, add sodium fluoride, heat and stir in a water bath at 80°C for 2 hours, stop heating, add sodium bicarbonate, disperse ultrasonically for 25 minutes, centrifuge, dry the solid phase, grind, and pass through a 150-mesh sieve to obtain the molding agent; the mass ratio of the material B, deionized water, sodium fluoride, and sodium bicarbonate is 20:300:1:2.
[0089] Comparative Example 3
[0090] The difference from Example 1 is that the mass ratio of sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium coconut oil, sodium lauryl polyoxyethylene ether sulfate, and sodium fatty acid methyl ester sulfonate in the mixed anionic surfactant is 0:9:2:1:2.
[0091] Comparative Example 4
[0092] The difference from Example 1 is that the mass ratio of sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium coconut oil, sodium lauryl polyoxyethylene ether sulfate, and sodium fatty acid methyl ester sulfonate in the mixed anionic surfactant is 9:0:2:1:2.
[0093] Comparative Example 5
[0094] The difference from Example 1 is that the mass ratio of sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium coconut oil, sodium lauryl polyoxyethylene ether sulfate, and sodium fatty acid methyl ester sulfonate in the mixed anionic surfactant is 5:4:0:3:2.
[0095] Comparative Example 6
[0096] The difference from Example 1 is that the mass ratio of sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium coconut oil, sodium lauryl polyoxyethylene ether sulfate, and sodium fatty acid methyl ester sulfonate in the mixed anionic surfactant is 5:4:2:0:3.
[0097] Comparative Example 7
[0098] The difference from Example 1 is that the mass ratio of sodium dodecyl sulfate, sodium α-olefin sulfonate, sodium coconut oil, sodium lauryl polyoxyethylene ether sulfate, and sodium fatty acid methyl ester sulfonate in the mixed anionic surfactant is 5:4:2:3:0.
[0099] Comparative Example 8
[0100] The difference from Example 1 is that the mass ratio of fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glycoside in the non-ionic surfactant is 0:9:1.
[0101] Comparative Example 9
[0102] The difference from Example 1 is that the mass ratio of fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glycoside in the non-ionic surfactant is 9:0:1.
[0103] Comparative Example 10
[0104] The difference from Example 1 is that the mass ratio of fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glycoside in the non-ionic surfactant is 6:4:0.
[0105] Comparative Example 11
[0106] The difference from Example 1 is that the mass ratio of protease, lipase, amylase, cellulase and pectinase in the biological enzymes is 0:12:5:2:2.
[0107] Comparative Example 12
[0108] The difference from Example 1 is that the mass ratio of protease, lipase, amylase, cellulase and pectinase in the biological enzyme is 12:0:5:2:2.
[0109] Comparative Example 13
[0110] The difference from Example 1 is that the mass ratio of protease, lipase, amylase, cellulase and pectinase in the biological enzyme is 11:6:0:2:2.
[0111] Comparative Example 14
[0112] The difference from Example 1 is that the mass ratio of protease, lipase, amylase, cellulase and pectinase in the biological enzymes is 6:6:7:0:2.
[0113] Comparative Example 15
[0114] The difference from Example 1 is that the mass ratio of protease, lipase, amylase, cellulase and pectinase in the biological enzymes is 6:6:5:4:0.
[0115] Performance Testing
[0116] The laundry fiber wrappings prepared in Examples 1-3 and Comparative Examples 1-15 were tested for detergency according to standard GB / T13174-2021. The test results are shown in Table 1 below.
[0117] Table 1
[0118]
[0119]
[0120] As can be seen from Table 1, the laundry fiber wrappings prepared in Examples 1-3 of the present application have excellent washing and decontamination effects;
[0121] In Comparative Example 1, the bentonite was not modified, and in Comparative Example 2, the fluorine-containing titanium dioxide was not doped, which would lead to a decrease in the adsorption of surfactants, green chelating agents, anti-redeposition agents, detergent aids, etc., resulting in a decrease in the decontamination effect of the prepared laundry fiber wrapping;
[0122] It can be seen from Comparative Examples 3-7 that the present application can significantly improve the decontamination effect through the synergistic effect of the various anionic surfactants added. Sodium dodecyl sulfate has good decontamination ability and good solubility, and can effectively remove stains. Sodium α-olefin sulfonate can increase the decontamination strength. Sodium cocoate can improve the overall performance of the detergent and increase the affinity of the detergent for grease. Sodium lauryl polyoxyethylene ether sulfate has good emulsifying properties and can help disperse grease in water and increase the cleaning power of the detergent. Sodium fatty acid methyl ester sulfonate can have an auxiliary synergistic effect with sodium dodecyl sulfate to improve the decontamination efficiency. The mixed anionic surfactant can reduce the surface tension of water, so that water can better penetrate into the stains, separate the stains from the fiber surface, and make grease stains easier to be washed away by water. Through these synergistic effects, the mixed anionic surfactant can significantly improve the decontamination ability of the detergent;
[0123] It can be seen from Comparative Examples 8-10 that the present application adds a variety of nonionic surfactants, and through the synergistic effect between fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glycoside, the fatty alcohol polyoxyethylene ether has a good solubilizing ability, can disperse the stains in water to form a stable emulsion, so that it is easier to be washed away by water, the fatty alcohol alkoxy compound has good interfacial activity, can reduce the interfacial tension between water and oil, so that the oil stains are more easily surrounded and removed by water molecules, and can penetrate into the interior of the fiber to dissolve or disperse stubborn stains, the alkyl glycoside can penetrate the fiber, and at the same time has a good dispersing ability, can remove water-soluble stains such as protein and starch, the complementary decontamination ability between fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glycoside, each of which works synergistically for different types of stains, increases the contact area between the stain and water, facilitates removal, improves the solubility of the stain in water, facilitates washing, penetrates into the interior of the fiber, effectively removes stubborn stains, and enhances the overall performance of the detergent;
[0124] It can be seen from Comparative Examples 11-15 that the present application adds a variety of biological enzymes, and through the synergistic effect of protease, lipase, amylase, cellulase, and pectinase, specifically, during the washing process, the addition of protease can decompose protein into smaller peptide chains and amino acids, lipase can decompose fat into glycerol and fatty acids, amylase can decompose starch into maltose and dextrin, cellulase can decompose cellulose to make it fluffy, pectinase can decompose pectin and destroy the cell wall structure, so that the stains are easier to be washed away by water. By adding a variety of enzymes, multiple types of stains can be targeted at the same time to improve the comprehensiveness of stain removal. After the protease decomposes the protein, the amino acids produced can be used as an emulsifier for lipase to help remove grease. The glucose produced by the amylase decomposing starch can be further used by microorganisms. The low molecular weight substances produced by the enzyme decomposition of stains usually have higher water solubility and are therefore easier to be washed away by water. The catalytic action of the biological enzyme is mild and will not damage the fiber structure of the clothes. It is suitable for various fabrics. The multi-enzyme combination not only improves the stain removal effect, but also extends the service life of the clothes.
[0125] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A formulation for a laundry fiber wrap having a high surfactant content, characterized in that: The formula includes the following raw materials in parts by weight: Mixed anionic surfactant 30-50 parts by weight Nonionic surfactant 20-30 parts by weight Green chelating agent 10-20 parts by mass Anti-redeposition agent 1-5 parts by weight 10-20 parts by weight of detergent Forming agent 10-20 parts by mass 1-5 parts by weight of biological enzyme Polyvinyl alcohol nonwoven fabric 5-10 parts by mass Polyethylene glycol 4000 50 parts by mass Cellulose 4-6 parts by weight 1-2 parts by mass of fatty acid.
2. A formulation of a laundry fiber wrap with a high surfactant content according to claim 1, characterized in that: The preparation method of the molding agent comprises the following steps: S1. Mix aluminum chloride hexahydrate, sodium hydroxide and deionized water, heat in a 60°C water bath with stirring, and then heat in a 60°C water bath and let stand to obtain material A; S2, taking the material A and the nano-bentonite, mixing them, heating them in a water bath at 60° C. with stirring, then heating them in a water bath at 60° C. and standing them, centrifuging them, washing the solid phase, drying it, grinding it, and sieving it to obtain the material B; S3, mixing ammonium fluoride, tetrabutyl titanate and anhydrous ethanol, stirring, adding glacial acetic acid and acetylacetone in sequence, continuing to stir, standing, filtering, washing and drying the solid phase, placing in a muffle furnace at 300-400° C. for 2-3 h, cooling, grinding, and sieving to obtain material C; S4, taking the material B and deionized water, mixing, ultrasonically dispersing, adding sodium fluoride, heating in a water bath at 80° C. with stirring, stopping heating, adding sodium bicarbonate, ultrasonically dispersing, centrifuging, taking the solid phase, drying, grinding, and sieving to obtain material D; S5. Mix the material C, material D and deionized water, disperse by ultrasonic, let stand, filter, wash and dry the solid phase to obtain the molding agent.
3. A formulation of a laundry fiber wrap with a high surfactant content according to claim 2, characterized in that: In step S1, the mass ratio of aluminum chloride hexahydrate, sodium hydroxide and deionized water is 1.2-1.4:0.9-1.1:
20.
4. A formulation of a laundry fiber wrap with a high surfactant content according to claim 2, characterized in that: In step S2, the dosage ratio of the material A and the nano-bentonite is 10-12 mL: 6-8 g.
5. A formulation of a laundry fiber wrap with a high surfactant content according to claim 2, characterized in that: In step S3, the dosage ratio of ammonium fluoride, tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, and acetylacetone is 1-1.6 g: 20-25 mL: 60-80 mL: 3-5 mL: 5-6 mL.
6. A formulation of a laundry fiber wrap with a high surfactant content according to claim 2, characterized in that: In step S4, the mass ratio of material B, deionized water, sodium fluoride and sodium bicarbonate is 20-25:300:1-3:2-4.
7. A formulation of a laundry fiber wrap with a high surfactant content according to claim 2, characterized in that: In step S5, the mass ratio of material C, material D and deionized water is 0.6-0.8:3-4:
50.
8. The formulation of a laundry fiber wrap with a high surfactant content according to claim 1, characterized in that: The polyvinyl alcohol nonwoven fabric is a fiber fabric made of polyvinyl alcohol with a polymerization degree of 500-800 and an alcoholysis degree of 80-90.
9. A formulation of a laundry fiber wrap with a high surfactant content according to claim 1, characterized in that: The mixed anionic surfactant includes sodium lauryl sulfate, sodium α-olefin sulfonate, sodium coconut oil, sodium lauryl alcohol polyoxyethylene ether sulfate and sodium fatty acid methyl ester sulfonate; The nonionic surfactant includes fatty alcohol polyoxyethylene ether, fatty alcohol alkoxy compound and alkyl glycoside; The green chelating agent includes trisodium methylglycine diacetate, tetrasodium glutamate diacetate, sodium citrate and sodium gluconate; The anti-redeposition agent includes sodium polyacrylate, maleic acid-acrylic acid polymer and polyethyleneimine homopolymer; The detergent builder includes sodium carbonate, sodium bicarbonate and sodium silicate.
10. A method for preparing a laundry fiber package with a high surfactant content, characterized in that: The preparation method of the laundry fiber package with high surfactant content comprises the following steps: Mixed anionic surfactant, nonionic surfactant, green chelating agent, anti-redeposition agent, detergent aid and forming agent according to the formula amount, stir, let stand, add polyethylene glycol 4000, cellulose and fatty acid, heat and stir at 50°C to obtain a viscous material, press the viscous material onto a polyvinyl alcohol nonwoven fabric, wait for the viscous material to cool to below 40°C, mix the biological enzyme evenly and spray it on the surface of the viscous material, press another polyvinyl alcohol nonwoven fabric on the surface of the viscous material, cool, slice and package to obtain the laundry fiber package with high surfactant content.